1996
DOI: 10.1152/ajpheart.1996.270.6.h2060
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II and contraction of isolated myocytes from human, guinea pig, and infarcted rat hearts

Abstract: The effects of angiotensin II on myocardial contractility were assessed in isolated cardiac myocyte preparations, using video microscopy with a computerized edge-detection system. Angiotensin II (1 nM-10 microM) did not affect the contraction of rat (n = 10), guinea pig (n = 11), or human ventricular myocytes (n = 8) or of human atrial myocytes (n = 12). Isoproterenol or raised extracellular calcium increased the contraction amplitude of the cardiac myocytes to a maximum of between 150 and 560% above basal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 0 publications
6
35
0
1
Order By: Relevance
“…Perhaps the most interesting result from our current study is the protected -adrenergic responsiveness in diabetic myocytes with concurrent IGF-I overexpression, suggesting that protection of -adrenergic responsiveness may play a role in IGF-I-induced cardiac protection. Our data is consistent with previous findings that isoproterenol increases the contraction amplitude and the velocities of contraction and relaxation in ventricular myocytes (Lefroy et al 1996). Inconsistent observations have been documented regarding the impact of diabetes on the -adrenergic system.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Perhaps the most interesting result from our current study is the protected -adrenergic responsiveness in diabetic myocytes with concurrent IGF-I overexpression, suggesting that protection of -adrenergic responsiveness may play a role in IGF-I-induced cardiac protection. Our data is consistent with previous findings that isoproterenol increases the contraction amplitude and the velocities of contraction and relaxation in ventricular myocytes (Lefroy et al 1996). Inconsistent observations have been documented regarding the impact of diabetes on the -adrenergic system.…”
Section: Discussionsupporting
confidence: 93%
“…The regulation of myocardial contractility by these receptor agonists has exhibited a wide range of species-dependent variation. While angiotensin II fails to affect contraction in rat, guinea pigs, or human atrial/ ventricular myocytes (Lefroy et al 1996), it produces a sustained negative response in adult mice (Sekine et al 1999). Both angiotensin II and phenylephrine have been shown to inhibit cell shortening but not intracellular Ca 2+ transients through a protein kinase C-dependent pathway in mouse cardiomyocytes (Sakurai et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These effects of catalase and compound C indicate a key role for H 2 O 2 in modulating the signaling pathway leading from Ang-II to eNOS phosphorylation and NO synthesis in cardiac myocytes. Ang-II has complex effects on cardiac and vascular function, and the direct effects of Ang-II on cardiac myocyte contractility appear to vary depending upon the specific experimental system being studied (25)(26)(27)(28). We found that Ang-II produces a positive inotropic effect on cardiac myocytes isolated from adult mice (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…The next day, cells were placed in the microscope stage incubator (Tokai), and HyPer2 fluorescence was excited with 420∕40 and with 500∕16 band-pass excitation filters; corresponding YFP emission was acquired every 5 s for 10 min using a 535∕30 band-pass emission filter. For calculating HyPer ratio images, CFP and YFP images were acquired; after background subtraction, the HyPer2 signal was quantitated as described above and as we have previous reported (27).…”
Section: Methodsmentioning
confidence: 99%
“…Angiotensin II-extracellular signal-regulated kinase signaling mediates insulin-like growth factor-I and endothelin-1 release Differently from what has been observed in other species, Ang II does not acutely enhance contractility of human and rat left ventricular myocytes [22][23][24][25]. In addition, Ang II 10-11 to 10-7 mol/l failed to elicit Ca 2þ influx responses in adult rat ventricular cardiomyocytes [26].…”
Section: Discussionmentioning
confidence: 74%